DEPRECIATION AS A FUNCTION OF REVENUE. - Nielsen, Oswald (The Accounting Review, 1938)
Abstract During recent years, when many businesses have reported heavy losses, some economists have accused accountants of erring in so generally charging depreciation on the straight-line basis. That accountants tend to overstate profits in periods of prosperity and to exaggerate losses during depressions is the opinion of those who maintain this viewpoint. These alternate overstatements of profits and losses, it is asserted, lead business managers and investors to assume respective attitudes of over- and under-confidence regarding prospects of business conditions. Therefore, accountants have been urged to forsake the straight-line method of making depreciation charges and, instead, to vary them with business activity. At times, some members of the accounting profession have advanced views of a similar, if not identical nature. From the economic viewpoint a capital asset is primarily a bundle of services receivable in the future and depreciation of the asset may be considered to be the conversion of these services into product values.